Measurement of Individual Value at Risk in a Small-Cap Stock Portfolio on the Indonesia Stock Exchange - I Nyoman Tri Arjana; Christimulia Purnama Trimurti; Gusti Ngurah Joko Adinegara; Yeyen Komalasari (Universitas KH. Abdul Chalim Mojokerto, 2026)
Small-cap stocks are characterized by high volatility and relatively low liquidity, which increase market risk exposure. This study aims to estimate individual Value at Risk (VaR) and examine the effect of stock volatility, liquidity, and stock returns on VaR in small-cap stock portfolios listed on the Indonesia Stock Exchange during 2020–2023. VaR is estimated using the Monte Carlo simulation approach with a 95% confidence level and one-year holding period. The study employs panel data regression with 120 firm-year observations. The results indicate that stock volatility has a positive and significant effect on VaR, stock returns have a negative and significant effect on VaR, while stock liquidity does not significantly affect VaR. Simultaneously, volatility, liquidity, and returns significantly explain VaR variation, with an adjusted R² of 0.688. These findings confirm that volatility is the primary determinant of downside risk in small-cap stocks. The study contributes to risk measurement literature in emerging markets and provides implications for portfolio risk management strategies.